Analisis Dampak Kriminalitas Terkait Narkoba - Lukman Salim Nur Hakim; Syafiq Ijlal Islami; Muhamad Giosefi; Asmak Ul Hosnah (JOURNAL SAINS STUDENT RESEARCH, 2024)
Drug abuse and its impact on criminal behaviour has become an issue of global concern. In 2022, East Java ranked first in the highest number of drug cases in Indonesia, followed by North Sumatra. Criminality is a social phenomenon that encompasses a wide range of lawlessness, with varying causal factors such as economic inequality, mental disorders, substance abuse, and education levels. Drug use is often associated with criminal acts, such as drug trafficking, theft to finance addiction, and drug-related acts of violence. The relationship between drugs and criminality varies depending on the accessibility of drugs, the socioeconomic status of the community, and the environment. Criminological research helps identify factors that influence this relationship and supports in designing effective strategies. This research uses qualitative analysis and literature review to understand the phenomenon of drugs and their impact on individuals and society. The study covers the classification of drugs based on legal regulations and their impact on physical and mental health. Prevention and treatment of drug dependence involves rehabilitation and counselling programmes to prevent drug use. Factors such as family breakdown, mass media, technological changes and economic imbalance influence an individual's decision to use drugs. Drug use also triggers mental disorders, and can lead to criminal behaviour that harms others and undermines trust within the community. These factors contribute to the risk of increased drug-related criminality.